Propuesta de instalación escultórica contemporánea tomando como referente la figura humana de los transeúntes en la cotidianidad de la ciudad de Loja - Yunga Saca, María Belén (2021)
The present investigation entitled: Proposal for a contemporary sculptural installation taking as a reference the human figure of passersby in the daily life of the city of Loja, is part of the artistic investigation of contemporary art, giving way to the analysis of the theoretical-aesthetic foundation, as well as techniques and materials for the construction of sculptural installations; The human figure has been taken as a managerial motif, through which experimentation is carried out with different sculptural alternatives and materials that allow the figure to be modeled to express the movement of each element. The present investigation is of a qualitative nature, the inductive, analytical, synthetic, historiographic and experimental methods were used; those that allowed to obtain the information, analyze it and support the sculptural work through the collection of bibliographic and documentary material. The works made based on the experimentation of materials and artistic techniques present the human figure of a grotesque character through sculptural installation, in turn seeking active interaction between work-spectator, showing the daily life of passers-by in the city of Loja.